Research advances in mechanism of antiangiogenic therapy combined with immune checkpoint inhibitors for treatment of non-small cell lung cancer - He, Danming; Wang, Lu; Xu, Jiachen; Zhao, Jie; Bai, Hua; Wang, Jie (Frontiers in Immunology, 2023)
Immunotherapy has changed the treatment strategy of non-small cell lung cancer (NSCLC) in recent years, among which anti-PD-1/PD-L1 antibodies are the most used. However, the majority of patients with NSCLC do not derive benefit from immune checkpoint inhibitors (ICIs). Vascular abnormalities are a hallmark of most solid tumors and facilitate immune evasion. Thus, combining antiangiogenic therapies might increase the effectiveness of anti-PD-1/PD-L1 antibodies. In this paper, the mechanisms of anti-angiogenic agents combined with anti-PD-1/PD-L1 antibodies are illustrated, moreover, relevant clinical studies and predictive immunotherapeutic biomarkers are summarized and analyzed, in order to provide more treatment options for NSCLC patients.